The Effect of Americano Caffeine on Concentration Levels Among Gen-Z - Ashodiki, Muhammad Amru; Artanty, Ary; Ramdhana, Rickadesti; Junaidi, Ahmad (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2024)
This study aims to determine the optimal dosage of Americano coffee consumption that enhances concentration without compromising health. Employing a quasi-experimental design with pretest and posttest measurements, this study analyzes the impact of Americano caffeine on the focus levels of Gen Z individuals. The study involved 30 Gen-Z respondents in Malang City, with a majority being female (17 individuals or approximately 56.7%) and predominantly aged 21 (10 individuals). Paired-sample t-test results revealed a significant increase in performance and concentration following Americano consumption. Data showed a reduction in task completion time and an increase in concentration scores, indicating substantial improvements in cognitive capabilities. Collectively, these findings suggest that Americano coffee consumption can be effective in enhancing both operational efficiency (response speed) and cognitive capability (accuracy and focus) in Gen-Z. This research is expected to encourage more mindful and healthier coffee consumption habits, supporting both mental and physical well-being.